Atratividade e palatabilidade de ração suplementada com leveduras e ração encapsulada na alimentação para alevinos de tilápia do Nilo (Oreochromis niloticus) - Fernandes, Vanessa Lopes (2024)
The objective of this research was to determine the attractiveness and palatability of yeast and encapsulated feed in feeding Nile tilapia fingerlings. Thus, two experiments were carried out, the first evaluated three experimental diets with the inclusion of sugar cane yeast, yeast extract and a control diet without yeast supplementation. In the second experiment, experimental diets containing encapsulated soy protein isolate, gum Arabic and maltodextrin and a control diet were evaluated. To carry out the experiment, 12 tilapia fries were distributed individually in aquariums with a capacity of 22 liters. The fish were fed, in the first experiment three times a day and in the second experiment four times a day, and the offers were randomly drawn beforehand, all fish received all experimental diets every day. 30 pellets were offered per feeding and with three minutes of recording, the following parameters were evaluated: time to capture the first pellet, number of rejections, number of approaches without capturing pellets and number of pellets consumed. Subsequently, the attractiveness and palatability index were calculated, the data obtained were subjected to parametric analysis of variance (ANOVA), performing Tukey's multiple comparison test at a 5% level of significance. Both experiments for the evaluated parameters showed no significant difference (P> 0.05) between the treatments evaluated for the Nile tilapia species. Pointing out that the experimental diets tested do not interfere with food acceptance.